PKM SOSIALISASI DAN COACHING CLINIC OLAHRAGA PANAHAN KEPADA SISWA SMP IT ALFITYAN SCHOOL GOWA - Akbar Yusuf; Suparman Suparman; Andi Sahrul Jahrir; Jonki Alexander (Program Studi Ilmu Keolahragaan, 2022)
Archery is a sport that requires special skills and high concentration to achieve target accuracy. The emphasis of this sport lies in the balance of the body which is also influenced by emotions. If we are in a depressed condition, we can guarantee that the oncoming arrow will not hit the target. Therefore, before releasing arrows, we should first regulate our emotions and calm down to reduce carelessness. For the material presented to students through outreach and Clinic Coaching by explaining the basic techniques in doing archery starting when standing with the body and hands, then how to hold the bow and arrow then explaining how to draw and aim at the target and release the arrow so that it fits with the targeted target. This Community Service Activity was created to carry out outreach and clinic coaching to students of SMPIT Al Fityan Gowa School. By providing a good basic archery technique starting in a standing position until releasing the arrow on the bow so that it hits the right target. But in archery what is needed is a very high concentration of course in balance with continuous and consistent practice.